One Health Approach on Dog Bites: Demographic and Associated Socioeconomic Factors in Southern Brazil - Constantino, Caroline; Da Silva, Evelyn Cristine [UNESP]; Dos Santos, Danieli Muchalak; Paploski, Igor Adolfo Dexheimer; Lopes, Marcia Oliveira; Morikawa, Vivien Midori; Biondo, Alexander Welker (MDPI, 2023)
Despite being an important public health issue, particularly due to rabies, dog bites and associated risk factors have rarely been assessed by health services from a One Health perspective. Accordingly, the present study aimed to assess dog biting and associated demographic and socioeconomic risk factors in Curitiba, the eighth-largest Brazilian city with approximately 1.87 million people, based on the post-exposure prophylaxis (PEP) rabies reports between January/2010 and December/2015. The total of 45,392 PEP reports corresponded to an average annual incidence of 4.17/1000 habitants, mainly affecting white (79.9%, 4.38/1000 population), males (53.1%, 4.81/1000 population), and children aged 0–9 years (20.1%, 6.9/1000 population), with severe accidents associated with older victims (p < 0.001) and mainly caused by dogs known to the victims. An increase of USD 100.00 in the median neighborhood income was associated with a 4.9% (95% CI: 3.8–6.1; p < 0.001) reduction in dog bites. In summary, dog biting occurrence was associated with victims’ low income, gender, race/color, and age; severe accidents were associated with elderly victims. As dog bites have been described as multifactorial events involving human, animal, and environmental factors, the characteristics presented herein should be used as a basis to define mitigation, control, and prevention strategies from a One Health perspective.
Keywords: associated factors; dog bites; human rabies prophylaxis; low income; spatial analysis